Financial Ratios as Performance Indicators: Empirical Analysis at PT. Bank Nagari Period 2019-2023 - Ananda Isa Salsabila Yanuarmana; Sanda Patrisia Komalasari (Management Institute Faculty of Economics Universitas Andalas, 2024)
This research aims to analyze PT Bank Nagari financial performance. Ratio analysis was used in this research for the 2019-2023 period. The research method used is a case study, where data is taken from PT Bank Nagari financial reports. PT Bank Nagari was analyzed using various financial ratios. Financial performance analysis is carried out by calculating liquidity, profitability and solvency ratios. The liquidity ratios analyzed include the Quick Ratio, Loan to Asset Ratio (LAR), and Loan to Deposit Ratio (LDR). The profitability ratios used are Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), and Net Interest Margin (NIM). Meanwhile, the solvency ratios analyzed include the Capital Adequacy Ratio (CAR) and debt-to-equity ratio (DER). The research results show that the financial ratio analysis of PT. Bank Nagari, during the 2019-2023 period, complies with applicable regulations and does not experience significant obstacles—the economic performance of PT. Bank Nagari shows consistent stability and improvement during the analysis period, reflecting the bank's ability to maintain its liquidity, profitability and solvency.